Estudo sobre a organização da produção em área de assentamento no Sudeste do Pará - MONTEIRO, Dion Márcio Carvaló (Universidade Federal do Pará, 2011)
This paper was developed in a rural workers site in the town of Parauapebas/PA, and it aimed: (01) identify, at the Palmares site, the main problems caused by the application of an agro-industrial economic reproduction model, what is weird in the southeast of the state of Pará (imported from the south of the country); (02) check some outcomes, mainly economic, but also the social ones that were caused by the current structure of the existing production organization in that site; and finally, (03) analyze the presumed conflict that there is between the collective production model, proposed by the MST*, and the individualized economic one, preferred by the rural workers. It was identified that the main obstacles in the attempt of forced insertion of an economic model that did not seem to contemplate the infrastructure and technological differences between these two regions occurred due to the lack of administrative and technical knowledge of most of the workers as well as their chiefs. Regarding the main obtained economic outcomes, it was verified that the main produced cultures were: rice, corn and cassava (being the latter commercialized in natura or in the form of flour), which are common in the region. As far as the collective and individualized production is concerned, it was noted that the structure of organization and management of the workers needs to be better developed so that this collective economic model really succeeds. The research considered a group of 517 families which were officially registered by the National Institute of Colonization and Agro Reform, where 105 family chiefs were interviewed and as a way to guarantee the research representativity. One at least or three families at the most were interviewed in each production nucleus. 38 going on nucleus were identified, which amount was found after counting before the association and nucleus coordinators, a questionnaire was applied to all these local heads. One of the outcomes of the research was: more than 95% of the families that were annexed to one of the production nucleus work in an individualized way and that almost 50% of the nucleus heads informed that there is very little cooperation among their directed structure components. The research also indicates that it is still necessary to advance in the investigations presented here, mainly in the definition and in the building of economic models that are able to accommodate individual productive activities as well as collective or cooperative ones in the country.